MiR-92b-3p Inhibits Proliferation of HER2-Positive Breast Cancer Cell by Targeting circCDYL - Liang, Gehao; Ling, Yun; Lin, Qun; Shi, Yu; Luo, Qing; Cen, Yinghuan; Mehrpour, Maryam; Hamai, Ahmed; Li, Jun; Gong, Chang (Frontiers in Cell and Developmental Biology, 2021)
Objectives: Circular RNA (circRNA) is a novel class of RNA, which exhibits powerful biological function in regulating cellular fate of various tumors. Previously, we have demonstrated that overexpression of circRNA circCDYL promoted progression of HER2-negative (HER2-) breast cancer via miR-1275-ULK1/ATG7-autophagic axis. However, the role of circCDYL in HER2-positive (HER2+) breast cancer, in particular its role in modulating cell proliferation, one of the most important characteristics of cellular fate, is unclear. Materials and methods: qRT-PCR and in situ hybridization analyses were performed to examine the expression of circCDYL and miR-92b-3p in breast cancer tissues or cell lines. The biological function of circCDYL and miR-92b-3p were assessed by plate colony formation and cell viability assays and orthotopic animal models. In mechanistic study, circRNAs pull-down, RNA immunoprecipitation, dual luciferase report, western blot, immunohistochemical and immunofluorescence staining assays were performed. Results: CircCDYL was high-expressed in HER2+ breast cancer tissue, compared with the adjacent normal tissue and other breast cancer subtypes. Overexpression of circCDYL promoted proliferation of HER2+ breast cancer cells but not through miR-1275-ULK1/ATG7-autophagic axis. CircRNA pull down and miRNA deep-sequencing demonstrated the binding of miR-92b-3p and circCDYL. Interestingly, circCDYL did not act as miR-92b-3p sponge, but was degraded in miR-92b-3p-dependent silencing manner. Clinically, expression of circCDYL and miR-92b-3p was associated with clinical outcome of HER2+ breast cancer patients. Conclusion: MiR-92b-3p-dependent cleavage of circCDYL was an essential mechanism in regulating cell proliferation of HER2+ BC cells. CircCDYL was proved to be a potential therapeutic target for HER2+ BC, and both circCDYL and miR-92b-3p may be potential biomarkers in predicting clinical outcome of HER2+ BC patients.